AUTONOMIA EPISTEMOLÓGICA DA EDUCAÇÃO FÍSICA - Nascimento, Tiago Alves do (2012)
Physical Education is historically constituted as a field devoid of an autonomous knowledge. This engendering of his field was a Physical Education colonized epistemologically other areas of knowledge. Some propositions of Physical Education sought to legitimize the Physical Education as an autonomous area.. This is the goal of this work: analyze these thesis whether the Physical Education have a epistemological autonomy. The method used was the literature review and field research hermeneutics. Was selected authors who propose to analyze the epistemological autonomy for Physical Education. When analyzing the data we found that the discourses of education open to an interpretation of epistemological autonomy as a field of intervention, producing expertise with an interest in solving immediate problems of reality unlike science studying the same object of Physical Education each one with its own statutes theorists, trying to describe, explain, mechanisms and patterns with no intention to intervene, improve, enhance, qualify that is specific to Physical Education.